Pengaruh Budaya Organisasi Terhadap Kinerja Pegawai Pada Sekretariat DPRD Kabupaten Ogan Ilir - Zein Ghozali; Munyati; Tutik Pebrianti; Vivin Afini; Arubina Bangsawan (JURNAL EKOBIS Kajian Ekonomi dan Bisnis, 2022)
This study aims to determine The Influence of Organizational Culture on Employee Performance at the DPRD Secretariat Ogan Ilir Regency. The research took samples using the Propotionate Sampling technique because employees at The DPRD Secretariat consists of Civil Servants, Non-Permanent Employees who proportionally stratified. The research method is done by testing relationship (associative hypothesis) two variables, namely variable X (Culture Organization) and variable Y (Employee Performance) with statistical tests using Product Moment Correlation. sample that used in this study were Civil Servants and Non-Civil Servants fixed as many as 65 respondents by filling out a Likert scale questionnaire. The results of Product Moment correlation calculations show that organizational culture greatly influences employee performance at the Ogan Ilir Regency DPRD Secretariat, this can be seen from the r test with 65 respondents and an error rate of 5%. Based on rtable = 0.2441 and rcount = 0.995 where rcount is in the correlation coefficient interval of 0.80 – 0.100 which indicates a very strong correlation. Then the value of rcount is greater than rtable (0.995> 0.2441) so that Ha is accepted Ho is rejected. This shows that there is a positive and significant relationship between organizational culture and employee performance. This relationship has an influence of 99% and the remaining 1% is the influence of other factors. From these results the researcher hopes that the Leaders at the DPRD Secretariat of Ogan Ilir Regency pay more attention to the organizational culture of employees so that they can improve employee performance.